Moving Forward in STEM Education, Challenges and Innovations in Senior High School in the Philippines: The Case of Northern Iloilo Polytechnic State College (Jurnal Pendidikan IPA Indonesia, 2019)
This qualitative research focused on school experiences of 20 females and 14 males senior high school (SHS) students majoring in science, technology, engineering and mathematics (STEM) in Northern Iloilo Polytechnic State College (NIPSC), the Philippines from Academic Year 2017-2018 and 2018-2019. This study aimed to identify both the positive and negative points on Senior High School (SHS)- Science, Technology, Engineering and Mathematics (STEM) track in terms of curriculum, instructional materials, laboratory equipment, faculty educational qualification, research output and courses to be taken in NIPSC of SHS-STEM students. Purposive sampling was used for the selection of the informants. Interview, focus group discussion, and observation were employed in the study. The students’ responses in the interview revealed teachers’ qualifications and their passion for enhancing SHS-STEM curriculum. Besides, the availability of facilities was a strong point of NIPSC as a model school in implementing STEM curriculum in the district. However, lack of time management for teachers to hold classes, limited science textbooks and classroom, and unavailability of the laboratory for hands-on activities need proper attention by concern authorities. Around 46% of SHS-STEM graduates take civil engineering at NIPSC because of the well-trained teachers, and the high rating in board examination. Also, the Commission on Higher Education (CHED) allowed non-STEM to enroll in science-related courses, and the Department of Science and Technology (DOST) allowed them to apply for the scholarship program. However, the bridging program is a waste of time, effort, and money for both teachers and students. NIPSC as a model school in SHS-STEM track has to enhance facilities as well as the guidance office to correctly assist students in future endeavors and to take courses similar to their tracks and interests.